Common genetic mechanisms implicated in Antibiotic Resistance - Ridwan Olamilekan Adesola; Ogundepo Oluwatobi Moses (Genetics & Applications, 2022)
Antibiotic resistance is conferred through a large pool of genes, which is now referred to as the resistome. The appearance of the ever-changing structure of a cistron in the macromolecule together with the key factors of primary mutations, and evolution that translates the ability to grow in the presence of antibiotics to microorganism is creating a natural selection, causing those who are vulnerable to scale back in population whereas those who have the flexibility to grow in the presence of antibiotics to flourish. In addition, mechanisms of horizontal gene switch transfer among bacteria of the same species and interspecies have been involved in the distribution of antibiotic resistant genes amenable for unique mechanisms which allow them to overwhelm antibiotics found in their on-the-spot surroundings among other organisms. The most horrifying aspect of these resistance genes is that their components are frequently deployed into the microbic community, which affects humans, thanks to the involvement of genetic level which expeditiously assist the mobilization and maintenance of those resistant genes. These genes include those that impact linezolid methyltransferases (cfr), aminoglycoside ribosomal methylases (armA, rtmB), efflux pumps giving fluoroquinolone resistance (qepA), and biofilm resistance all of which are related to antimicrobial-producing bacteria. This work aims to reveal and discuss the various identified genetic mechanisms used by antibiotic-resistant bacteria.